THE EFFECT OF COMPETENCY AND HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS A MEDIATION VARIABLE AT PT. TRIO KENCANA, PARIGI MOUTONG REGENCY, CENTRAL SULAWESI, INDONESIA - Nur Indah; Alamsyah Alamsyah; M. Amsyahar; Astri Aryanti Amsyahar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze and test the influence of competence and human resource development on employee performance, as well as to examine the role of job satisfaction as a mediating variable in this relationship. The background of this study is based on the importance of human resource quality as the main asset of the organization, where employee performance is a determinant of the success of achieving company goals. Problems that often arise are suboptimal employee competence, ineffective HR development programs, and suboptimal job satisfaction levels which ultimately have an impact on declining performance. This study uses a quantitative approach with a survey method. The population in this study were all employees at PT. TRIO KENCANA, with a sample of 500 people determined using the Slovin formula and taken through the Proportional Stratified Random Sampling technique. Data were collected through the distribution of questionnaires that have been tested for validity and reliability. Data analysis techniques used include descriptive analysis, classical assumption tests, multiple linear regression analysis, and path analysis to test the mediating role with the help of SPSS 25 software. The results of the study indicate that partially and simultaneously, the variables of competence and human resource development have a positive and significant influence on employee job satisfaction. Furthermore, competence, human resource development, and job satisfaction have also been shown to have a positive and significant influence on employee performance. The results of the path analysis prove that job satisfaction is able to mediate the relationship between competence and human resource development on employee performance. This means that the higher the level of competence and the better the implemented HR development program, the higher the employee job satisfaction will be, which will ultimately have an impact on improving employee performance significantly. Job satisfaction is a key factor that bridges employee capabilities and company development programs to the work results achieved. Recommendations that can be given to company management are the need to improve competency standards through tiered training, refine clear career development programs, and create a conducive work environment so that employee job satisfaction is maintained and organizational performance continues to improve.